Refleksi Sosial Dalam Novel Gadis Pantai Karya Pramoedya Ananta Toer (Kajian Sosiologi Sastra: Alan Swingewood) - Satya Wirayudha; Aswandikari; Johan Mahyudi (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2024)
This research aims to describe the social reflections contained in the novel Pantai Girl by Pramoedya Ananta Toer. Data collection in this research was carried out by reading and marking which refers to social reflection between characters in the novel Pantai Girl by Pramoedya Ananta Toer. The results of this research found that the social reflection contained in the novel Pantai Girl consists of familial relationships, oppression of women, class differences (poor and rich, rulers and those ruled), human relationships with other people in coastal areas. This poverty incident includes a lack of income in coastal areas far from the city. Apart from that, the novel Pantai Girl contains things that exist in human relationships with other people.